2008
DOI: 10.1029/2008gb003294
|View full text |Cite
|
Sign up to set email alerts
|

Predicting export of dissolved organic carbon from forested catchments in glaciated landscapes with shallow soils

Abstract: [1] This study presents a simple model of dissolved organic carbon (DOC) loading to surface waters that is applicable to headwater catchments in forested regions on glaciated landscapes. Average annual DOC export was highly variable among the 33 experimental catchments along an east-west transect, ranging from 0.90 to 13.74 g C/m 2 /a. It was hypothesized that the proportion of wetlands within the catchments would explain the majority of variation in average annual DOC export. To test this hypothesis, digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 51 publications
5
97
0
Order By: Relevance
“…Supporting this idea, instantaneous DOC concentration was higher at the valley-bottom stream than at the hillslope streams (Grimola and Ef-4) during both the transition and wet periods. Similarly, other studies have reported higher stream DOC concentration for catchments with wetlands and riparian zones than for catchments without them (Hinton et al, 1998;Inamdar and Mitchell, 2006;Creed et al, 2008). Other parts of the catchment could act as DOC sources to the valley-bottom stream; yet, the fact that the two hillslope streams had similar DOC concentration suggests a consistent source of DOC through the FSW hillslopes.…”
Section: Riparian Vegetation As a Source Of Dissolved Organic Matter mentioning
confidence: 86%
“…Supporting this idea, instantaneous DOC concentration was higher at the valley-bottom stream than at the hillslope streams (Grimola and Ef-4) during both the transition and wet periods. Similarly, other studies have reported higher stream DOC concentration for catchments with wetlands and riparian zones than for catchments without them (Hinton et al, 1998;Inamdar and Mitchell, 2006;Creed et al, 2008). Other parts of the catchment could act as DOC sources to the valley-bottom stream; yet, the fact that the two hillslope streams had similar DOC concentration suggests a consistent source of DOC through the FSW hillslopes.…”
Section: Riparian Vegetation As a Source Of Dissolved Organic Matter mentioning
confidence: 86%
“…In many areas, increasing DOC in surface waters has been reported and variously ascribed to the effects of reduced acid precipitation, changes in land management, climate change and increased drought frequency (Laudon et al 2012). Given climate trajectories and increased land use change in northern regions, predictive models are needed to inform managers of potential water quality changes, including DOC from peat-covered catchments (Dillon and Molot 1997;Creed et al 2003;Creed 2008). These approaches need to conceptualise the soil biogeochemical processes that generate DOC with hydrological transport mechanisms that connect sources to the stream network.…”
Section: Discussionmentioning
confidence: 99%
“…Blanket peat tends to form on impermeable rocks or thick layers of glacial till on shallow slopes (typically <10°, although slopes up to 25°have been noted) where saturated conditions are allowed to develop because of impeded and/or slow drainage (Taylor 1983). In other wetland areas, topography has been used to map the distribution of saturated areas in topographic hollows and floodplains (Creed et al 2008, Debella-Gilo & Etzelmüller 2009). However, blanket peat tends not to be confined to hollows or footslopes and is often found on hill-top plateaus (Taylor 1983).…”
Section: Limitationsmentioning
confidence: 99%